2019
DOI: 10.1039/c8md00608c
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of an intramolecular hydrogen bonding motif in the side chain of antimalarial benzimidazoles

Abstract: Analogues of a novel class of benzimidazoles with an intramolecular hydrogen bonding motif have been synthesized and evaluated in vitro for their antiplasmodium activity against chloroquine-sensitive (NF54) and multi-drug resistant (K1) strains of the human malaria parasite Plasmodium falciparum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…However, a reduction in activity was observed for all compounds when assessed against a chloroquine‐resistant strain, indicating a degree of cross sensitivity. While β‐hematin inhibition assays did not correlate with anti‐plasmodial activity, the most promising compound from this study ( 59 ) was found to have superior β‐hematin inhibitory activity to chloroquine, indicating that inhibition of this pathway likely contributes the anti‐plasmodial activity of these compounds …”
Section: Antimalarial Agentsmentioning
confidence: 64%
See 1 more Smart Citation
“…However, a reduction in activity was observed for all compounds when assessed against a chloroquine‐resistant strain, indicating a degree of cross sensitivity. While β‐hematin inhibition assays did not correlate with anti‐plasmodial activity, the most promising compound from this study ( 59 ) was found to have superior β‐hematin inhibitory activity to chloroquine, indicating that inhibition of this pathway likely contributes the anti‐plasmodial activity of these compounds …”
Section: Antimalarial Agentsmentioning
confidence: 64%
“…Atram et al., designed a series of related compounds, featuring a basic nitrogen, in close enough proximity to a hydroxy functionality to facilitate the formation of intramolecular hydrogen bonds . The shielding of hydrogen bond donors and acceptors from interacting with water as a result of intramolecular hydrogen bonds reduces the energy penalty of desolvation, which would usually occur as a result of moving from an aqueous to a lipid environment .…”
Section: Antimalarial Agentsmentioning
confidence: 99%
“…In particular, the exhibition of the internal hydrogen bond between the phenolic hydroxyl and amino nitrogen groups is crucial for the antiplasmodial activity of α-aminocresols. [21] Additionally, Chinnapattu et al found that constraining the rotatability of the bond between the α-carbon and the amino nitrogen atom by introducing an amide bond led to a decrease in activity of the resulting compounds. [20] Therefore, in order to comprehensively elucidate the structure-activity relationship (SAR) profile of the pursued ferrocenyl α-aminocresols, the phenolic hydroxy group (OH) and the rotatable α-CÀ NH bond were modified by synthesizing non-phenolic benzylamines 12 a-d and salicylamides 14 a-g as non-rotatable aminocresol congeners, respectively.…”
Section: Synthesismentioning
confidence: 99%
“…[19] Additionally, α-aminocresols have attracted renewed research interest in the recent years as antimalarial agents. [20,21] By conjugating the adamantane motif to the α-aminocresol scaffold, Chinnapattu et al generated a series of adamantane aminomethylphenols (4) with 3D geometry possessing impressive plasmocidal activity against chemosusceptible (NF54) and multidrug-resistant (K1) Plasmodium falciparum strains in the nanomolar range. [20] Similarly, Chibale and co-workers incorporated the α-aminocresol moiety into the benzimidazole scaffold to produce α-aminocresol-benzimidazole conjugates (5) that were active against the same strains of the malaria parasite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation